1977
DOI: 10.1136/adc.52.8.638
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of pethidine and bupivacaine in the newborn.

Abstract: SUMMARY Pethidine or an epidural injection of bupivacaine are common forms of obstetric analgesia in Britain. Bupivacaine has been thought to have little effect on the fetus, but neurobehavioural studies have cast doubt on this. We therefore investigated the elimination of these drugs by babies in similar population groups. Bupivacaine was largely eliminated in just over one day, while pethidine required between 2 and 6 days. This could account for the persisting depression in babies whose mothers had received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1978
1978
1989
1989

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…In addition, Caldwell et al (f 978) found a positive correlation between CIM ratio and time from pethidine administration to delivery. Cooper et al (1977) have pointed out that although neonates whose mothers received pethidine within I hour of delivery had the highest blood COlt-· centrations, they also had minimum depression. All of these data are consistent with the hypothesis that significant amounts of pethidine cross from mother to fetus over a period of several hours.…”
Section: Placental Transfermentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, Caldwell et al (f 978) found a positive correlation between CIM ratio and time from pethidine administration to delivery. Cooper et al (1977) have pointed out that although neonates whose mothers received pethidine within I hour of delivery had the highest blood COlt-· centrations, they also had minimum depression. All of these data are consistent with the hypothesis that significant amounts of pethidine cross from mother to fetus over a period of several hours.…”
Section: Placental Transfermentioning
confidence: 96%
“…On the basis of their urinary excretion data, Hogg et al (I 977) estimated approximately 60 hours would be required to eliminate 95 % of pethidine from these neonates. Cooper et al (1977) and Caldwell et al (1978) studied concentrations of pethidine in I 9 and I 0 neonates respectively whose mothers had received pethidine during labour. Cooper et al (J 977) estimated that neonates took from 3 to 6 days to completely eliminate the drug, while Caldwell et al (I 978) estimated the 'elimination' half-life to be 22.7 (SD ± 10) hours.…”
Section: The Neonatementioning
confidence: 97%
“…Despite this frequent but careful use of pethidine, our results confirm that significant depression of respiratory function was produced in these babies and, although slight, the differences were still apparent 12-24 hours after delivery. The fact that the effects of pethidine can be detected for even longer has been confirmed by Cooper et al (1977) who found that it may take the newborn 3 to 6 days finally to eliminate the drug. Although not presented in detail, the respiratory function results were divided according to the pethidine-to-delivery time interval, and more obvious respiratory depression was found when the pethidine had been administered more than one hour before delivery.…”
Section: Discussionmentioning
confidence: 86%
“…depression. Furthermore pethidine readily crosses the placenta and yet the neonate is less well able to dispose of the drug than is the mother (Cooper, Stephen & Aggett, 1977). The average neonatal elimination half-life has been estimated to be 22 h which is approximately 7 times longer than that of healthy adults (Caldwell et al, 1978).…”
Section: Preliminary Studies On the Disposition Of Meptazinol In The mentioning
confidence: 99%